A brush up on water quality studies of Port Dickson, Malaysia. - Praveena, Sarva Mangala; Siraj, Siti Shapor; Suleiman, Ahmad Kimon; Aris, Ahmad Zaharin (Academic Journals, 2011)
Port Dickson is the only coastal district in Negeri Sembilan, Malaysia which is a favourite weekend getaway for people from Malaysia as well as Singapore. Impacts of tourism activities, shipping, refineries, land reclaiming activities, coastal zone management construction and insufficient sewage water treatment are the most pressing environmental problems that have caused deterioration of water quality in Port Dickson. Thus, bearing in mind all the impacts towards water quality of Port Dickson, water quality studies related to Port Dickson are briefly reviewed. This is to provide an overall viewpoint of current situation of water quality status, identify and prioritize future studies and regulatory plans in Port Dickson. Extensive Port Dickson water quality studies were done from 1999 to 2002 so far, Port Dickson waters have been analyzed in terms of physico-chemical parameters, nutrients, organic carbon, microbiological and heavy metals to indicate environmental pollution. However, limited studies were available on heavy metal concentration in coastal waters of Port Dickson. After 2002, fewer studies were conducted in terms of water quality in Port Dickson. This review output showed that water quality related studies in Port Dickson are clearly needed to be increased and strategized in terms of research objectives. Looking into pollution factors in Port Dickson, accumulation of heavy metals in water, sediment and biomonitors studies are crucial at this point of time. Future studies on heavy metals are crucial to understand impacts of different ecological compartments from various anthropogenic sources. Future studies in Port Dickson should also give a focus in utilization of this resource in order fill in the knowledge gap and provide clear direction in sustainable development of this precious resource. Amid these findings, real extent of contamination in Port Dickson will give direction helpful recommendations on environmental management and pollution control in this area.